Cameroon : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper examines infrastructure needs in Cameroon and makes policy recommendations to address them. In doing this, it provides advice to strengthen the public investment management framework, including public-private partnerships (PPP). The paper reviews the recent experience with public investment and PPPs and discusses policy options: increasing spending on public investment through traditional public procurement, while preserving fiscal sustainability; increasing the efficiency of public investment institutional processes; and increasing reliance on private-sector participation in infrastructure, while properly addressing their associated fiscal risks. Infrastructure indicators in Cameroon trail those of regional peers. Despite a slight improvement in the overall quality of infrastructure in 2013, infrastructure indicators remain low when compared to other sub-Saharan African countries, especially for roads, air transport, and electricity. A large body of theoretical and empirical work finds a positive relationship between public investment and growth. Physical and social infrastructure is widely considered to be a critical input for economic growth, productivity, and welfare.